Pentamidine in Pneumocystis jirovecii prophylaxis in heart transplant recipients - Diken, Adem Ilkay (World J Transplant, 2016)
Despite advances in transplantation techniques and the quality of post-transplantation care, opportunistic infections remain an important cause of complications. Pneumocystis jirovecii (P. jirovecii) is an opportunistic organism, represents an important cause of infections in heart transplantation patients. Almost 2% to 10% of patients undergoing cardiac transplantation have Pneumocystis pneumonia. Prophylaxis is essential after surgery. Various prophylaxis regimes had been defined in past and have different advantages. Trimethoprim/sulfamethoxazole (TMP/SMX) has a key role in prophylaxis against P. jirovecii. Generally, although TMP/SMX is well tolerated, serious side effects have also been reported during its use. Pentamidine is an alternative prophylaxis agent when TMP/SMX cannot be tolerated by the patient. Structurally, pentamidine is an aromatic diamidine compound with antiprotozoal activity. Since it is not effectively absorbed from the gastrointestinal tract, it is frequently administered via the intravenous route. Pentamidine can alternatively be administered through inhalation at a monthly dose in heart transplant recipients. Although, the efficiency and safety of this drug is well studied in other types of solid organ transplantations, there are only few data about pentamidine usage in heart transplantation. We sought to evaluate evidence-based assessment of the use of pentamidine against P. jirovecii after heart transplantation.